Pelatihan Penggunaan Alat Peraga Matematika bagi Guru SD GMIT Koro’oto, Kupang, Nusa Tenggara Timur - Kristoforus Djawa Djong; Yohanes Ovaritus Jagom; Samuel Igo Leton; Yohana Rina Rowa; Irmina Veronika Uskono; Wilfridus Beda Nuba Dosinaeng; Meryani Lakapu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Props are aids used to ease students understand well the mathematical concepts explained by the teacher. The elementary school level requires real concepts so that in concretizing abstract concepts the teacher should be able to use props to explain the concept. The purposes of the community service are teachers are able to produce props in learning activities and can instill basic concepts so that they are able to solve commonly faced problems in learning activities. The method used is a practical method. This community service was carried out at SD GMIT Koro’oto, Kupang Regency, East Nusa Tenggara. Based on the evaluation result of the community service, it shows that teachers participated actively in the activity shown by their responses and interactions. In addition, the teachers felt the importance of this training because they gained a lot of new knowledge in solving every problem in learning activities and were able to produce props that could help explain basic concepts to students.